2011
DOI: 10.1186/1465-9921-12-80
|View full text |Cite
|
Sign up to set email alerts
|

Weight and metabolic effects of cpap in obstructive sleep apnea patients with obesity

Abstract: BackgroundObstructive sleep apnea (OSA) is associated with obesity, insulin resistance (IR) and diabetes. Continuous positive airway pressure (CPAP) rapidly mitigates OSA in obese subjects but its metabolic effects are not well-characterized. We postulated that CPAP will decrease IR, ghrelin and resistin and increase adiponectin levels in this setting.MethodsIn a pre- and post-treatment, within-subject design, insulin and appetite-regulating hormones were assayed in 20 obese subjects with OSA before and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 50 publications
(54 reference statements)
3
63
1
Order By: Relevance
“…12 Furthermore, in a small randomized controlled study, Garcia et al observed a small amount of weight gain in 20 obese OSA subjects over the course of 6 months. 13 Our study extends these latter findings by documenting weight gain with CPAP in a much larger cohort and showing that it is a function of adherence. Thus, our findings and those of previous studies suggest that CPAP is inducing a state of positive energy balance resulting in weight gain.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…12 Furthermore, in a small randomized controlled study, Garcia et al observed a small amount of weight gain in 20 obese OSA subjects over the course of 6 months. 13 Our study extends these latter findings by documenting weight gain with CPAP in a much larger cohort and showing that it is a function of adherence. Thus, our findings and those of previous studies suggest that CPAP is inducing a state of positive energy balance resulting in weight gain.…”
Section: Discussionsupporting
confidence: 63%
“…However, the levels of adherence in this study are similar to those in other long-term randomized controlled trials. 13,14,32 Furthermore, given our current findings, greater adherence would likely have made the differences in weight between CPAP and Sham even more striking. Second, in comparison to the CPAP group, more participants in the Sham group failed to complete the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of them was randomized clinical trial (RCT) [19], the remaining studies were observational [20][21][22][23][24][25][26][27][28][29]. One study [27] reported results separately for obese group and non-obese group.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%